A New Path of Thinking for Europe? Care for Life, Personhood, and the Place of Thought in Roberto Esposito - D’Angelo, Diego (Political theology, 2022)
The philosophy of Roberto Esposito has recently been taking a new path. After a first phase that started an original discussion about the concepts of the “impolitical,” he dedicated, in a second phase, more and more attention to questions linked to the concepts of “person” and “personhood” in a critical vein. In the present contribution, I claim that his attempt to avoid such traditional categories to define the human being as a political subject is deeply related to the concept of care, most notably to what I propose to term care of and for life itself. In his last work, which inaugurates a third and new phase, Da fuori. Una filosofia per l’Europa, his reflections focus on the question of how Europe thinks, and sketch out the role of contemporary so-called “Italian Theory” in the framework of today’s European thinking. The question of care will therefore be related, in the last part of the present paper, to the problem of understanding the role of though in contemporary Europe.